Analisis Audit Internal Sumber Daya Manusia Pada PT. Perkebunan Nusantara VII Unit Baturaja - Muhammad Arif Muttaqin; Jusmani Jusmani; Nurmala Nurmala (Universitas PGRI Palembang, 2023)
ABSTRACT This review means to test the speculation of the impact of representative work fulfillment, hierarchical correspondence, authoritative rivalry, and initiative style on the interior review of HR. The populace in this study were all workers at PT. Nusantara VII Plantation Baturaja Unit. The strategy in this study utilizes clear factual strategies, in particular measurements used to break down information by depicting or portraying every one of the information that has been gotten and afterward making ends from the examination acquired, with research information investigation methods utilizing SPSS (Statistical Product and Service Solutions). The consequences of the speculation test presumed that at the same time showed that worker work fulfillment, hierarchical correspondence, hierarchical rivalry, and initiative style had a critical (+) impact on the inward review of HR. Incomplete outcomes likewise show that representative work fulfillment, hierarchical correspondence, authoritative rivalry, and initiative style have a critical (+) impact on inside review of HR. This is proven by the worth of Fcount > Ftable (17,147 > 3.23) with an importance worth of 0.000 < 0.001 which implies Ho is dismissed and Ha is acknowledged. The worth of occupation fulfillment tcount > ttable (3.966 > 1.684) with an importance worth of 0.000 <0.05, and that implies Ho is dismissed and Ha is acknowledged. Hierarchical correspondence esteem tcount > ttable (5.642 > 1.684) with an importance worth of 0.000 <0.05, and that implies Ho is dismissed and Ha is acknowledged. Hierarchical contest esteem tcount > ttable (6.524 > 1.684) with an importance worth of 0.000 <0.05, and that implies Ho is dismissed and Ha is acknowledged. What's more, the worth of initiative style tcount > ttable (7,707 > 1,684) with an importance worth of 0.000 <0.05, and that implies Ho is dismissed and Ha is acknowledged. Keywords: Human Resources Internal Audit, Employee Job Satisfaction Audit, Communication Audit Organization, Organizational Competition Audit, Leadership Style Audit. ABSTRAK Tinjauan ini dimaksudkan untuk menguji spekulasi dampak pemenuhan pekerjaan pekerja, korespondensi otoritatif, kontes hierarkis, dan gaya inisiatif pada tinjauan interior SDM. Populasi dalam penelitian ini adalah seluruh pekerja PT. Perkebunan Nusantara VII Unit Baturaja. Strategi dalam penelitian ini menggunakan strategi elucidating terukur, yaitu pengukuran khusus yang digunakan untuk menguji informasi dengan menggambarkan atau menggambarkan setiap informasi yang didapat, dengan prosedur pemeriksaan informasi penelitian menggunakan SPSS (Statistical Product and Service Solutions). Hasil uji hipotesis menyimpulkan bahwa secara simultan menunjukkan bahwa kepuasan kerja karyawan, komunikasi organisasi, kompetisi organisasi, dan gaya kepemimpinan berpengaruh (+) Signifikan terhadap audit internal sumber daya manusia. Hasil secara parsial juga menunjukkan bahwa kepuasan kerja karyawan, komunikasi organisasi, kompetisi organisasi, dan gaya kepemimpinan berpengaruh (+) Signifikan terhadap audit internal sumber daya manusia. Hal tersebut dibuktikan dengan nilai Fhitung > Ftabel (17,147 > 3,23) dengan nilai signifikansi yaitu 0,000 < 0,001 yang berarti Ho ditolak dan Ha diterima. Nilai kepuasan kerja thitung > ttabel (3,966 > 1,684) dengan nilai signifikansi 0,000 < 0,05 yang berarti Ho ditolak dan Ha diterima. Nilai komunikasi organisasi thitung > ttabel (5,642 > 1,684) dengan nilai signifikansi 0,000 < 0,05 yang berarti Ho ditolak dan Ha diterima. Nilai kompetisi organisasi thitung > ttabel (6,524 > 1,684) dengan nilai signifikansi 0,000 < 0,05 yang berarti Ho ditolak dan Ha diterima. Dan nilai gaya kepemimpinan thitung > ttabel (7,707 > 1,684) dengan nilai signifikansi 0,000 < 0,05 yang berarti Ho ditolak dan Ha diterima. Kata kunci: Audit Internal Sumber Daya Manusia, Audit Kepuasan Kerja Karyawan, Audit Komunikasi Organisasi, Audit Kompetisi Organisasi, Audit Gaya Kepemimpinan.